GrinchGEF - a novel Rho-specific guanine nucleotide exchange factor - Winkler, Stefan; Mohl, Marion; Wieland, Thomas; Lutz, Susanne (Biochemical and biophysical research communications, 2005)
RhoGTPases, which are activated by specific guanine nucleotide exchange factors (GEFs), play pivotal roles in several cellular functions. We identified a new RhoGEF (GrinchGEF) containing the typical Dbl homology domain, a putative WD40-like domain, and two predicted transmembrane helices. In contrast to most other RhoGEFs, it exhibits no sequence similarities to known pleckstrin homology domains. GrinchGEF mRNA was highly abundant in skeletal muscle and pancreas. Despite the predicted transmembrane domains, subcellular localization studies revealed a cytosolic distribution. In vitro, GrinchGEF induced the GDP/GTP exchange at RhoA, but not at Rac1 or Cdc42. In intact cells, GrinchGEF induced specifically Rho activation and enhanced RhoA-C-specific downstream effects.